The motivation in elementary school students and the beliefs and attitudes of parents - Martinelli, Selma de Cássia (2011)
Scientific literature about motivation in education is considerably growing in the last two decades. Family is being considered as an important variable in studies related to apprenticeship procedure at school. Considering the importance of these variables, this paper has as a purpose described possible relations between student’s mot ivations and his parent’s beliefs and attitudes. In this study took part 262 elementary school students from 3° and 5° grades of both sexes e his parents. It was used two evaluating scales: the Scholar Motivation Evaluated Scale (EAME-IJ) and the Parents Beliefs and Attitude Evaluated Scale (EACAP). This paper’s results had shown a correlation between student’s motivation and the parents beliefs.